Funding Disparities and the Inequitable Distribution of Teachers: Evaluating Sources and Solutions - Adamson, Frank; Darling-Hammond, Linda (Education Policy Analysis Archives, 2012)
The inequitable distribution of well-qualified teachers to students in the United States is a longstanding issue. Despite federal mandates under the No Child Left Behind Act and the use of a range of incentives to attract teachers to high-need schools, the problem remains acute in many states. This study examines how and why teacher quality is inequitably distributed, by reviewing research and examining data on school funding, salaries, and teacher qualifications from California and New York—two large states that face similar demographic diversity and educational challenges. Using wage adjustments to control for cost of living differentials, we find that both overall school funding and teacher salary levels are highly inequitable both across and within states – generally exhibiting a ratio of 3 to 1 between high- and low-spending jurisdictions.  Furthermore, low-salary districts serve students with higher needs, offer poorer working conditions, and hire teachers with significantly lower qualifications, who typically exhibit higher turnover. We find that districts serving the highest proportions of minority and low-income students have about twice as many uncredentialed and inexperienced teachers as do those serving the fewest. In an elasticity analysis, we find that increases in teacher salaries are associated with noticeable decreases in the proportions of teachers who are newly hired, uncredentialed, or less well educated. These teacher qualifications, in turn, are associated with student achievement, holding student characteristics constant. We review research on strategies that have been largely unsuccessful at addressing this problem, such as “combat pay” intended to recruit teachers to high need schools, suggesting that small bonuses might be productive if added to an equitable salary structure where working conditions are comparable, but may be inadequate to compensate for large differentials in salaries and working conditions.  We review studies illustrating successful policy strategies in states that have taken a more systemic approach to equalizing salaries, raising teaching standards, and providing supports for teacher learning and school development. We recommend federal initiatives that could provide stronger supports and incentives for equalizing students’ access to well-qualified and effective teachers, including equalizing allocations of ESEA resources across states, enforcing existing ESEA comparability provisions for ensuring equitable funding and equally qualified teachers to schools serving different populations of students, evaluating progress on resource equity in state plans and evaluations under the law, and requiring states to meet standards of resource equity – including the availability of well-qualified teachers – for schools identified as in need of improvement.